Membangun akuntabilitas manajerial: Perpaduan antara prinsip syariah dan akuntansi modern dalam praktik pengelolaan keuangan BAZNAS - Alifiyah, Azzahra Lulu (Maliki Interdisciplinary Journal, 2025)
This article discusses the importance of building managerial accountability through a combination of sharia principles and modern accounting in the context of BAZNAS financial management. As an institution that manages public funds, BAZNAS is required not only to obey formal rules, but also to maintain public trust spiritually. This article uses literature studies and normative reviews of the Qur’an and Hadith, which are then compared with modern managerial accounting principles. The results of the study show that values ​​such as amanah, honesty (ṣidq), and responsibility (hisab) are very much in line with the principles of transparency, accountability, and efficiency in the modern accounting system. The integration of these two approaches can strengthen public trust and improve the effectiveness of zakat institution governance. This article suggests strengthening sharia values ​​in the managerial and reporting processes, so that BAZNAS is not only legally valid, but also ethically and spiritually meaningful.